Adenylate kinase 1 deficiency disrupts mouse sperm motility under conditions of energy stress. Issue 5 (3rd August 2020) - Xie, Minyu; Zhang, Guofei; Zhang, Hanbin; Chen, Feilong; Chen, Yan; Zhuang, Yuge; Huang, Zicong; Zou, Feng; Liu, Min; An, Geng; Kang, Xiangjin; Chen, Zhenguo
Abstract: Mammalian spermatozoa are highly polarized cells characterized by compartmentalized cellular structures and energy metabolism. Adenylate kinase (AK), which interconverts two ADP molecules into stoichiometric amounts of ATP and AMP, plays a critical role in buffering adenine nucleotides throughout the tail to support flagellar motility. Yet the role of the major AK isoform, AK1, is still not well characterized. Here, by using a proteomic analysis of testis biopsy samples, we found that AK1 levels were significantly decreased in nonobstructive azoospermia patients. This result was further verified by immunohistochemical staining of AK1 on a tissue microarray. AK1 was found to be expressed in post-meiotic round and elongated spermatids in mouse testis and subsequent mature sperm in the epididymis. We then generated Ak1 knockout mice, which showed that AK1 deficiency did not induce any defects in testis development, spermatogenesis, or sperm morphology and motility under physiological conditions. We further investigated detergent-modeled epididymal sperm and included individual or mixed adenine nucleotides to mimic energy stress. When only ADP was available, Ak1 disruption largely compromised sperm motility, manifested as a smaller beating amplitude and higher beating frequency, which resulted in less effective forward swimming. The energy restriction/recover experiments with intact sperm further addressed this finding. Besides, decreased AK activity was observed in sperm of a male fertility disorder mouse model induced by cadmium chloride. These results cumulatively demonstrate that AK1 was dispensable for testis development, spermatogenesis, or sperm motility under physiological conditions, but was required for sperm to maintain a constant adenylate energy charge to support sperm motility under conditions of energy stress. Abstract : AK1 is required for sperm to maintain a constant adenylate energy charge to support sperm motility under conditions of energy stress.